Implementation of Green Open Space Policy in the Urban Area of Malinau - Cainie Cainie; Riswanda Riswanda; Lia Kian (International Journal Labs, 2023)
Malinau Regent Regulation Number 6 of 2021 Concerning Detailed Spatial Planning (RDTR) for Urban Areas of Malinau Regency Year 2021-2041 is a guideline for implementing development programs and policies in the Malinau urban area which covers several villages within the administrative area of ??Malinau Kota District, North Malinau District, and West Malinau District. To prove suitability and find out the factors that determine the implementation of green open space policies in the Malinau urban area based on the provisions in Article 25 regarding the city's green open space zone, it is necessary to conduct research on policy implementation using the variables proposed by George C. Edward III which includes communication, resources, commitment, and bureaucratic structure. Based on the research that has been conducted, it is evident that the implementation of the green open space policy in the Malinau urban area is not in accordance with the Regent's Regulation Number 6 of 2021 concerning Detailed Spatial Plans for the Malinau Urban Area 2021-2041. In addition, it is also known that communication is a determining factor in demonstrating the success of synergy between institutions to implement green open space policies in the Malinau urban area. So it needs to be optimized so that the policy can be implemented properly.